Śmierć małych drapieżców – „zwierzęce” pisarstwo Krystyny Kofty - Witczak, Krzysztof (Zoophilologica. Polish Journal of Animal Studies, 2019)
The article presents the problem of animal death in the perspective of contemporary posthuman research in the field of animal studies. Manifestations of animal characters were discussed on the example of works by a contemporary Polish writer – Krystyna Kofta. Selected topics from Kofta’s works (Kot, Syf and Pawilon małych drapieżców) serve to illustrate the relationship between the fate of a woman and an animal as victims of patriarchal culture.